Sticking with the old seed: Input value chains and the challenges to deliver genetic gains to smallholder maize farmers - Rutsaert, Pieter; Donovan, Jason (SAGE Publications, 2020)
The Kenyan maize seed sector exhibits high hybrid adoption rates, a growing number of seed companies, and an extensive agro-dealer network. Nonetheless, maize yields remain low and uptake of new, stress-tolerant varieties has been disappointing. This article investigates interactions in maize seed value chains in Kenya, and decisions made by agro-dealers, farmers, and seed companies, to gain a better understanding of how to encourage the uptake of new, stress-tolerant varieties. Data were collected during the 2019 seed-purchasing season from Kenyan seed companies (n = 8), agro-dealers (n = 80), and farmers immediately following their seed purchase (n = 466). Most agro-dealers had a wide offer of seed products available, but seed companies’ engagement with them was limited and marketing efforts were directly focused on farmers. Only a fraction of farmers used the agro-dealer environment to guide their decision-making. However, when agro-dealers engaged with farmers, they influenced varietal selection in 80% of the cases. Agro-dealers were one of the key information outlets about maize seed varieties. Seed company engagement with agro-dealers and in-store promotions (push marketing) should be further explored to improve returns on investments in seed systems.